Effect of nivolumab vs bevacizumab in patients with recurrent glioblastoma: the checkmate 143 phase 3 randomized clinical trial - Reardon, David A.; Brandes, Alba A.; Omuro, Antonio; Mulholland, Paul; Lim, Michael; Wick, Antje; Baehring, Joachim; Ahluwalia, Manmeet S.; Roth, Patrick; Bähr, Oliver; Phuphanich, Surasak; Sepulveda, Juan Manuel; et al. (JAMA oncology, 2020)
This randomized clinical trial examines the effect of programmed cell death 1 immune checkpoint inhibition with nivolumab on overall survival for patients with recurrent glioblastoma.